Knowledge, Attitudes and Practices of Maternity Health Workers Regarding Breast Self- Examination in the Governmental Hospitals at Sana’a City, Yemen (Thamar University Journal of Natural & Applied Sciences, 2023)
Background: Breast cancer is the most common cause of cancer death among women worldwide. Breast self-examination (BSE) is a simple very low cost and non-invasive adjuvant screening method for the detection of early breast cancer in women. Accordingly, women who correctly practice breast self-examination monthly are more likely to obtain better treatment and survival rate. Aim: This study aimed to assess maternity health workers’ knowledge, attitudes and practices (KAP) regarding breast self-examination in Sana’a city, Yemen. Methods: A cross-sectional study was conducted, and self-administered structured questionnaire was adapted to collect data from a convenient sample. Informed verbal consent was obtained from participants. Confidentiality of information was maintained throughout the study. KAP survey was carried out among 168 maternity health workers from governmental hospitals. Results: It was found that 56.5% know about BSE and 50.0% know that it should be performed monthly. The majority (93.5%) believed that BSE is important for early detection of breast cancer. However, only 50.7% perform BSE monthly and 59.2% performed at the second week of menstrual cycle. Conclusion: Unfortunately, almost only half of the study subject knows about BSE and how many times it should be performed and again only half of them performed monthly. Therefore, there is need for awareness creation on the benefits of BSE as an early detection for breast cancer among female health workers.